Jawabanmu

2014-05-07T22:23:03+07:00
Y =x² - 2x - 3
m1 = 2x - 2

2y + x - 6 = 0
2y = - x + 6
y = -1/2 x + 3
m2 = -1/2

syarat saling tegak lurus jika m1m2 = -1
                                             (2x - 2)(-1/2) = -1
                                                   2x - 2 = 2
                                                     2x = 4
                                                       x = 2
y = -1/2x + 3 ⇔y = -1 + 3 = 2

Persamaan garis melalui titik (2,2) dan m2=-1/2 adalah sbb:
y - y1 = m2(x - x1)
y - 2 = -1/2(x - 2)
y = -1/2x + 1 + 2
y = -1/2 x + 3